Increasing Digital Literacy Through the Use of Basic Technology for Youth Organizations on Indigenous Plants - Suciati, Rizkia; Nurhanifah, Siti; Halim, Zuhri; Andi, Andi (Indonesia Berdaya, 2024)
The use of technology is increasingly widespread and even dominates every human activity. The importance of digital literacy to deal with the negative impacts of technological advances is the basis for digital literacy in environmental and cultural conservation. This community service activity aims to improve digital literacy knowledge through the use of basic technology in the introduction of potential indigenous plants. Community service activities are carried out by empowering 18 youth organization (Karang Taruna). The method used during the activity is project-based learning based on natural history. The initial activity is to provide a pre-test and education on the introduction and use of plant applications. Furthermore, participants practice identifying and processing the information that has been obtained, so that local plant information is created in the form of a QR Code. Finally, an evaluation is carried out by providing a post-test. Training in the use of basic digital literacy technology for indigenous plants can increase the digital literacy knowledge of Karang Taruna’s member from 43.75% to 82.75%. With this increased knowledge, it is hoped that Karang Taruna can utilize basic technology to recognize indigenous plants as a form of environmental conservation and local cultural history.